A Highly Efficient and Photostable Photosensitizer with Near‐Infrared Aggregation‐Induced Emission for Image‐Guided Photodynamic Anticancer Therapy. Issue 33 (3rd July 2017) - Wu, Wenbo; Mao, Duo; Hu, Fang; Xu, Shidang; Chen, Chao; Zhang, Chong‐Jing; Cheng, Xiamin; Yuan, Youyong; Ding, Dan; Kong, Deling; Liu, Bin
Abstract : Photodynamic therapy (PDT), which relies on photosensitizers (PS) and light to generate reactive oxygen species to kill cancer cells or bacteria, has attracted much attention in recent years. PSs with both bright emission and efficient singlet oxygen generation have also been used for image‐guided PDT. However, simultaneously achieving effective 1 O2 generation, long wavelength absorption, and stable near‐infrared (NIR) emission with low dark toxicity in a single PS remains challenging. In addition, it is well known that when traditional PSs are made into nanoparticles, they encounter quenched fluorescence and reduced 1 O2 production. In this contribution, these challenging issues have been successfully addressed through designing the first photostable photosensitizer with aggregation‐induced NIR emission and very effective 1 O2 generation in aggregate state. The yielded nanoparticles show very effective 1 O2 generation, bright NIR fluorescence centered at 820 nm, excellent photostability, good biocompatibility, and negligible dark in vivo toxicity. Both in vitro and in vivo experiments prove that the nanoparticles are excellent candidates for image‐guided photodynamic anticancer therapy. Abstract : An aggregation‐induced emission (AIE) photosensitizer with near‐infrared emission is synthesized via precise molecular design. The nanoparticles based on the AIE photosensitizer show effective singlet‐oxygen generation, near‐infrared fluorescence, excellent photostability, good biocompatibility, and negligible dark in vivo toxicity, which make them excellent candidates for image‐guided photodynamic anticancer therapy.